Democratic decentralization in contemporary times: the new local government code of the Philippines - Panganiban, Elena M. (1995)
Decentralization has been espoused by the country's government leaders since the distant past. It was looked upon as a means of improving the delivery and performance of basic services and functions of local governments through the devolution of the inherent powers and responsibilities formerly held by the different departments and agencies carrying out similar duties at the local government levels. With the passage of the Local Government Code of 1991, it was presupposed that the transfer of duties and functions from the center to the periphery would be as smooth as silk. Such was not the case. There were emerging problems and areas of reform that cover mainly two dimensions of local governance; democracy and efficiency
Keywords: Urban development - Philippines; Local government - Philippines; Local government